Common variable immunodeficiency–associated endotoxemia promotes early commitment to the T follicular lineage - Le Coz, Carole; Bengsch, Bertram; Khanna, Caroline; Trofa, Melissa; Ohtani, Takuya; Nolan, Brian E.; Henrickson, Sarah E.; Lambert, Michele P.; Kim, Taylor Olmsted; Despotovic, Jenny M.; Feldman, Scott; Fadugba, Olajumoke O.; et al. (Journal of allergy and clinical immunology, 2019)
Although chiefly a B-lymphocyte disorder, several research groups have identified common variable immunodeficiency (CVID) subjects with numeric and/or functional TH cell alterations. The causes, interrelationships, and consequences of CVID-associated CD4+ T-cell derangements to hypogammaglobulinemia, autoantibody production, or both remain unclear. We sought to determine how circulating CD4+ T cells are altered in CVID subjects with autoimmune cytopenias (AICs; CVID+AIC) and the causes of these derangements. Using hypothesis-generating, high-dimensional single-cell analyses, we created comprehensive phenotypic maps of circulating CD4+ T cells. Differences between subject groups were confirmed in a large and genetically diverse cohort of CVID subjects (n = 69) by using flow cytometry, transcriptional profiling, multiplex cytokine/chemokine detection, and a suite of in vitro functional assays measuring naive T-cell differentiation, B-cell/T-cell cocultures, and regulatory T-cell suppression. Although CD4+ TH cell profiles from healthy donors and CVID subjects without AICs were virtually indistinguishable, T cells from CVID+AIC subjects exhibited follicular features as early as thymic egress. Follicular skewing correlated with IgA deficiency–associated endotoxemia and endotoxin-induced expression of activin A and inducible T-cell costimulator ligand. The resulting enlarged circulating follicular helper T-cell population from CVID+AIC subjects provided efficient help to receptive healthy donor B cells but not unresponsive CVID B cells. Despite this, circulating follicular helper T cells from CVID+AIC subjects exhibited aberrant transcriptional profiles and altered chemokine/cytokine receptor expression patterns that interfered with regulatory T-cell suppression assays and were associated with autoantibody production. Endotoxemia is associated with early commitment to the follicular T-cell lineage in IgA-deficient CVID subjects, particularly those with AICs. [Display omitted]